Differential processing of intrinsic vs. extrinsic coordinates in wrist movement: connectivity and chronometry perspectives - Martinez-Tejada, Laura Alejandra; Imakura, Yuji; Cho, Ying-Tung; Minati, Ludovico; Yoshimura, Natsue (Frontiers in Neuroinformatics, 2023)
This study explores brain-network differences between the intrinsic and extrinsic motor coordinate frames. Using brain fMRI data of isometric right wrist flexions and extensions performed in two forearm postures, a connectivity model showing the frame difference was obtained by machine-learning-based neural representation and effective functional connectivity using psychophysiological interaction and dynamic causal modeling analyses. The model indicated the network difference wherein the inferior parietal lobule receives extrinsic information from the rostral lingual gyrus through the superior parietal lobule and transmits intrinsic information to the Handknob, whereas extrinsic information is transmitted to the Handknob directly from the rostral lingual gyrus. A behavioral experiment provided further evidence on the difference between motor coordinate frames showing onset timing delay of muscle activity of intrinsic coordinate-directed wrist movement compared to extrinsic one. These results suggest that, if the movement is externally directed, intrinsic coordinate system information is bypassed to reach the primary motor area.